Educational Impact of a Structured Radiation Oncology Clerkship Curriculum: An Inter-Institutional Comparison - Oskvarek, Jonathan J. (J Am Coll Radiol, 2016)
PURPOSE: Many medical school clerkships have structured curricula, however most radiation oncology clerkships do not. The Radiation Oncology Education Collaborative Group (ROECSG) implemented a curriculum for fourth-year radiation oncology clerkships at 14 institutions. We hypothesized that students completing clerkships with the curriculum would report greater subjective knowledge and comfort to function as a radiation oncology resident compared with students completing clerkships without the curriculum. METHODS AND MATERIALS: The ROECSG curriculum included three 1-hour lectures and a 1-hour hands-on radiation treatment planning workshop. Applicants to a single radiation oncology residency program in the 2014–2015 academic year were sent an anonymous, validated clerkship experience survey. Students indicated if clerkships were completed at a curriculum site. Likert-type data (1=not at all, 5=extremely) are reported as median(interquartile range). RESULTS: Respondents described 276 clerkship experiences of which 64(23.2%) were completed at a curriculum site. Students whose first clerkship was at a curriculum site perceived greater post-clerkship confidence in knowledge of radiation biology (3 (3–4) vs 2(2–3), p<0.01), treatment set-up/positioning (3(2–3) vs. 2(2–3), p<0.05), treatment planning (3(2–3) vs. 2(2–3), p<0.01), and ability to integrate evidence-based medicine into treatment (4(2–4) vs. 3(2–4), p<0.05). Students who completed any clerkship with the curriculum had greater post-clerkship confidence to function as a radiation oncology resident (3(3–4) vs. 3(2–3), p<0.05). CONCLUSIONS: These results support the curriculum’s ability to increase student knowledge in radiation oncology, especially in the students’ first clerkship. Further, these findings suggest that expanded implementation of such curricula may ensure a rewarding educational experience during radiation oncology clerkships.